2009
DOI: 10.1007/s10290-009-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

How will growth in China and India affect the world economy?

Abstract: Export growth, Terms of trade, China, India, General equilibrium, F11, F12, F43, F47,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
4
20
0
Order By: Relevance
“…These results corroborate the conclusion of Dimaranan et al. (), whose simulations revealed that Chinese growth would intensify competition in manufacturing product markets, and that manufacturing industries from several countries would be negatively affected. Coefficients estimated by 2SLS of the other model's variables present the expected sign and are statistically significant in 1%.…”
Section: The Impact Of Chinese Exports On Global Exportssupporting
confidence: 91%
See 2 more Smart Citations
“…These results corroborate the conclusion of Dimaranan et al. (), whose simulations revealed that Chinese growth would intensify competition in manufacturing product markets, and that manufacturing industries from several countries would be negatively affected. Coefficients estimated by 2SLS of the other model's variables present the expected sign and are statistically significant in 1%.…”
Section: The Impact Of Chinese Exports On Global Exportssupporting
confidence: 91%
“…However, the GTAP model depends on a large set of parameters to simulate forecasts for the desired period, and is very responsive to the adopted parameters, which can significantly alter results, as seen in Dimaranan et al. (). In this study, an extension of the gravitational model capable of controlling several effects that impact bilateral trade, without depending on constraints presented by the GTAP model, was used.…”
Section: Methodological Aspects and Gravitational Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in both the developed economies and the growing Asian developing economies wage distribution effects were shown to depend on capital-skill complementarity (Tyers & Yang, 2000;Winchester & Greenaway, 2007). 6 Subsequent assessments include that by Dimaranan, Ianchovichina, and Martin (2009), which finds gains and losses across other developing regions stemming from growth in China and India, but only small net effects on the developed regions. Francois and Wignaraja (2008) use a similar approach to focus on the implications for the industrial economies of expanded intra-Asian trade.…”
Section: Global General Equilibrium Analysismentioning
confidence: 99%
“…At the same time, one may argue that until 2050 there will be considerable global population growth and most of the output growth will come from Asia-including China and India. In these countries, emphasis on fighting global warming is not naturally a top priority, rather economic catching-up figures prominently in the political system are; and economic analysis suggests that China and India still have a large potential for economic catching-up and long term growth, respectively (Dimaranan et al 2009). Nevertheless, one may emphasize that economic globalization also creates new opportunities for international technology transfer and for trade with environmental (green) goods.…”
Section: Introductionmentioning
confidence: 98%